Internal and external loads in professional women’s Rugby Sevens:analysis of a block-based training session with small games - Oliveira Bicudo, Filipe; Savassi Figueiredo, Lucas; Cambri, Lucieli Teresa; Ferreira, Jacielle Carolina; da Silva Azevedo, Ana Paula; Ferreira Pedrosa, Gustavo; da Silva Aguiar, Samuel; de Oliveira Castro, Henrique (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. This study aimed to compare internal load (IL) and external load (EL) variables between blocks of a game-basedRugby Sevens training session.Methods. A descriptive cross-sectional study design was employed. Twenty-eight professional athletes from the first divisionof the Brazilian national championship were monitored during a game-based training session, which consisted of varyingdurations of ball-in-play blocks. The training session comprised 4 blocks of 1 min, 2 blocks of 2 min, and 1 block of 3 minof ball-in-play, with 1-min intervals between blocks of the same duration and 2-min intervals between blocks of differentdurations.Results. A reduction in EL was reported during longer bouts of ball-in-play. Specifically, a reduction was observed whencomparing block 5 to block 1 (p = 0.021) and when comparing block 7 with blocks 1, 2, 3, 4, and 6 for distance per min. Foraccelerations and decelerations, blocks 5, 6, and 7 showed lower values than block 1 (p = 0.001 and p = 0.005, respectively).Block 4 showed an increase in rate of perceived exertion (RPE) values compared to blocks 1 (p = 0.010) and 2 (p = 0.004).Increased RPE values were also found in block 5 compared to block 1 (p = 0.001), as well as compared to blocks 2 (p = 0.001)and 3 (p = 0.002). RPE in block 7 was higher than in blocks 1, 2, 3, and 4 (p = 0.001).Conclusions. In summary, higher RPE values were reported across blocks, and IL appeared to be more volume-dependent.
Keywords: small-sided games; external load; internal load; female Rugby Sevens; performance monitoring